Mechanical stimulation promotes MSCs healing the lesion of intervertebral disc annulus fibrosus - Deng, Rongrong; Kang, Ran; Jin, Xiaoyu; Wang, Zihan; Liu, Xin; Wang, Qing; Xie, Lin (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stem cells (MSCs) and scaffolds offer promising perspectives for annulus fibrosus (AF) repair. The repair effect was linked to features of the local mechanical environment related to the differentiation of MSCs. In this study, we established a Fibrinogen-Thrombin-Genipin (Fib-T-G) gel which is sticky and could transfer strain force from AF tissue to the human mesenchymal stem cells (hMSCs) embedded in the gel. After the Fib-T-G biological gel was injected into the AF fissures, the histology scores of intervertebral disc (IVD) and AF tissue showed that Fib-T-G gel could better repair the AF fissure in caudal IVD of rats, and increase the expression of AF-related proteins including Collagen 1 (COL1), Collagen 2 (COL2) as well as mechanotransduction-related proteins including RhoA and ROCK1. To clarify the mechanism that sticky Fib-T-G gel induces the healing of AF fissures and the differentiation of hMSCs, we further investigated the differentiation of hMSCs under mechanical strain in vitro. It was demonstrated that both AF-specific genes, including Mohawk and SOX-9, and ECM markers (COL1, COL2, aggrecan) of hMSCs were up-regulated in the environment of strain force. Moreover, RhoA/ROCK1 proteins were also found to be significantly up regulated. In addition, we further -demonstrated that the fibrochondroinductive effect of the mechanical microenvironment process could be significantly blocked or up-regulated by inhibiting the RhoA/ROCK1 pathway or overexpressing RhoA in MSCs, respectively. Summarily, this study will provide a therapeutic alternative to repair AF tears and provide evidence that RhoA/ROCK1 is vital for hMSCs response to mechanical strain and AF-like differentiation.